Which Emergent Medication Should I Give Next? Repeated Use of Emergent Medications to Treat Acute Agitation - Searles Quick, Veronica B.; Herbst, Ellen D.; Kalapatapu, Raj K. (Frontiers in Psychiatry, 2021)
Agitation is a common symptom encountered among patients treated in psychiatric emergency settings. While there are many guidelines available for initial management of the acutely agitated patient, there is a notable dearth of guidelines that delineate recommended approaches to the acutely agitated patient in whom an initial medication intervention has failed. This manuscript aims to fill this gap by examining evidence available in the literature and providing suggested algorithms for sequential medication administration in patients with persistent acute agitation in psychiatric emergency settings. We discuss risk factors for medication-related adverse events and provide options for patients who are able to take oral medications and for patients who require parenteral intervention. We conclude with a discussion of the current need for well-designed studies that examine sequential medication options in patients with persistent acute agitation.